CEO overconfidence and tax practices: Does board gender diversity matter? - Lakhal, Faten; Khemiri, Sabrina; Bacha, Sami; Guizani, Assil (Management international / International Management / Gestiòn Internacional, 2023)
This study examines the effect of chief executive officer (CEO) overconfidence on tax avoidance practices. Based on a sample of French-listed firms, the results show that overconfident CEOs engage in high levels of tax avoidance suggesting that the overconfidence bias may lead CEOs’ to behave unethically and use deceitful tactics to avoid taxes. However, board gender diversity mitigates this behavior suggesting that female directors are good monitors on the board. Our findings give insights to policymakers who may consider gender diversity on top management positions in addition to the board of directors to prevent a loss in tax revenues.